Method for testing synergistic effect of mutual solvent and surfactant for well cementation
Through the testing method of using mutual solvents and surfactants in oil field cementing construction, the problem of reducing flushing effect caused by oil-based mud residue is solved, and the effect of improving the cementing environment and improving the cementing quality is achieved.
Patent Information
- Application Number
- CN202411916249.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-24
- Publication Date
- 2025-04-11
AI Technical Summary
During oil field cementing construction, oil-based mud remains between the first and second interfaces of the annex, resulting in a reduced flushing effect of the pre-liquid, affecting the cementing environment of the annex cement ring, and thus reducing the cementing quality.
The synergistic effect of mutual solvents and surfactants is used to evaluate its synergistic effect at different dosage ratios by designing rinsing fluids of different formulas, including formulas containing only surfactants, only surfactants or both surfactants and mutual solvents.
Through this test method, the synergistic effect of mutual solvents and surfactants can be accurately evaluated, the replacement efficiency of cementing construction can be improved, the cementing environment of the annular interface can be improved, and the cementing quality can be improved.
Smart Images

Figure CN119804572A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of oilfield cementing construction, and in particular to a testing method for the synergistic effect of a mutual solvent and a surfactant for cementing. Background Art
[0002] During the cementing construction in the oil field, the oil-based mud will remain between the first and second interfaces of the annulus to form oil slurry and oil film, which will reduce the flushing effect of the pre-fluid, resulting in the cementing environment of the cement ring in the annulus being affected. In order to flush the oil-based mud mixture attached to the first and second interfaces of the annulus, prevent the oil-based mud and the cement slurry of the cementing from directly contacting and contaminating each other, improve the cementing environment of the annulus interface, and improve the cementing quality, it is necessary to design a double-effect pre-fluid technology for the compound use of a mutual solvent and a surfactant, the surfactant of the technology should have a certain shear force and viscosity under normal temperature and high temperature, and it is not necessary to add other materials, but to use the suspension ability of the active substance itself and the mutual solvent to adjust the rheological properties of the double-effect pre-fluid, and the test method involving the synergistic effect of the mutual solvent and the surfactant in the present invention is used to test the synergistic effect of the two, and maximize the displacement efficiency of the cementing construction. At present, there is no test method in this field. Summary of the invention
[0003] The purpose of the present invention is to provide a testing method for the synergistic effect of mutual solvent and surfactant for cementing in view of the above-mentioned defects in the prior art, which has low cost, easy equipment modification, simple testing procedure and high detection accuracy.
[0004] The present invention provides a method for testing the synergistic effect of a mutual solvent and a surfactant for cementing, and the technical scheme thereof is: comprising the following process: First, the flushing liquid is prepared according to the designed formula, and the formula containing only surfactant, only mutual solvent, or both surfactant and mutual solvent is designed, and the formula with different addition ratios of the two is designed to facilitate the comparison of the synergistic effect; Secondly, prepare oil-based mud and use mud with different oil-water ratios for comparison; in addition, heat the oil-based mud according to site requirements, and pour the flushing liquid into the test cup for testing after high-temperature curing; Then, the prepared flushing liquid is added to the oil-based mud in batches in a quantitative manner. The conductivity of the non-conductive oil-based mud is 0 μs / cm. When the conductivity becomes the conductivity of the water-based mixture and is greater than 800 μs / cm, the synergistic effect of the mutual solvent and the surfactant is quantitatively evaluated by adding the flushing liquid volume ratio.
[0005] Preferably, the flushing solution is subjected to a wetting test by adding only the mutual solvent KCM036, and its formula is as follows: 0gal KCM035+2gal KCM036+40gal water; KCM036 is ethylene glycol monobutyl ether; The sample density of oil-based mud is 1.38 g / cm 3 , solid phase volume content is 44%, oil phase volume is 45%, and water phase volume is 11%.
[0006] Preferably, the above-mentioned flushing liquid adopts the wetting test with only the surfactant KCM035 added, and its formula is as follows: 2gal KCM035+0gal KCM036+40gal water, wherein KCM035 is a non-ionic composite surfactant.
[0007] Preferably, the wettability test of the above-mentioned flushing solution is carried out by adding a surfactant and a mutual solvent to the flushing solution at the same time. The formula is: 1gal KCM035+2gal KCM036+39gal water, KCM035 is a non-ionic composite surfactant, and KCM036 is ethylene glycol monobutyl ether.
[0008] Preferably, the wettability test of the above-mentioned flushing solution is carried out by adding a surfactant and a mutual solvent to the flushing solution at the same time. The formula is: 2gal KCM035+4gal KCM036+39gal water, KCM035 is a non-ionic composite surfactant, and KCM036 is ethylene glycol monobutyl ether.
[0009] Preferably, the above-mentioned nonionic composite surfactant has lipophilic and hydrophilic amphiphilic properties, the lipophilic group thereof is composed of a long-chain hydrocarbon group, and the hydrophilic group is a polyoxyethylene ether.
[0010] Preferably, the long-chain hydrocarbon group includes a siloxane group and a straight-chain alkyl group.
[0011] The mud cake of oil-based mud will adsorb the surfactant in the prepared aqueous solution containing surfactant and mutual solvent. The outer surface of the mud cake adsorbs one end of the hydrophobic group, and the hydrophilic part penetrates into the water. The water molecules and solvent in the solution are dissolved in the oil-based mud to cause swelling, and the cohesion and structural force of the mud cake of the oil-based mud are weakened. At the same time, the mutual force between the casing wall and the mud cake in the oil-based mud is also weakened. Then, under the flushing of the surfactant and mutual solvent, on the one hand, the mud cake in the oil-based mud will be gradually peeled off, and on the other hand, the mud cake in the oil-based mud will gradually roll up, and new swelling and wetting will occur. The new surface formed in the rolling process is immediately adsorbed by the surfactant molecules. Finally, the mud cake is completely rolled up on the interface, and the micelles formed by the two will wrap the washed oil-based mud, thereby dispersing it in the aqueous solution.
[0012] The test method for the synergistic effect of the mutual solvent and surfactant for cementing mentioned in the present invention comprises the following specific steps: 1) Prepare the flushing solution according to the recipe; 2) Measure 100 ml of uniform oil-based mud V0 and put it into the mixing cup; 3) The conductivity meter's electrodes should be inserted into the oil-based mud, and the oil-based mud should not pass through the electrodes; 4) Turn on the speed regulator start switch of the stirring device and adjust the speed to the liquid level and vortex; 5) After the conductivity meter test results are stable, read the conductivity reading of the oil-based mud; 6) Add V ml of flushing fluid to the oil-based mud and record the conductivity data until the reading stabilizes; 7) Calculate according to the formula: V%=V*100% / (V+V0); Wherein, V%, is the percentage of power washing volume to total liquid volume, %; V, volume of flushing solution added, ml; V0, oil-based mud volume, ml.
[0013] Compared with the prior art, the beneficial effects of the present invention are as follows: The present invention evaluates the wetting ability of the water-based spacer fluid on the oil-based drilling fluid by continuously testing the conductivity of the mixture under the experimental temperature and shear rate. The specific principle is that the oil-based drilling fluid is non-conductive, while the water-based spacer fluid is conductive. When a variable amount of water-based spacer fluid is added to a quantitative amount of oil-based drilling fluid, the conductivity of the stirred mixture will change. This change can be measured by numbers, and the influence of different added amounts of surfactants and mutual solvents on the reversal rate is evaluated by volume ratio. In addition, the present invention can accurately and quantitatively evaluate the oil-water phase change of the oil-based drilling fluid after being acted upon by the isolation fluid and the flushing fluid, and evaluate the wetting ability of the isolation fluid or the flushing fluid by continuously detecting the conductivity of the drilling fluid under heating (normal pressure) and shearing. This method can test the synergistic effect of the interaction between surfactants and mutual solvents. The evaluation method of the present invention is effective, simple to operate, has a low manufacturing cost, and is easy to implement. BRIEF DESCRIPTION OF THE DRAWINGS
[0014] Figure 1 It is a schematic structural diagram of the silicone rubber heating plate of the present invention; Figure 2 It is a structural schematic diagram of a speed regulating stirring device; Figure 3 is the wetting reversal volume percentage curve of Example 1; Figure 4 is the wetting reversal volume percentage curve of Example 2; Figure 5is the wetting reversal volume percentage curve of Example 3; Figure 6 is the wetting reversal volume percentage curve of Example 4; Figure 7 This is the compatibility test curve of the spacer fluid and cement slurry; In the above picture: power supply 1, wire 2, temperature controller 3, silicone plate heating 4, speed regulator 5, mixing cup 6. DETAILED DESCRIPTION
[0015] The preferred embodiments of the present invention are described below in conjunction with the accompanying drawings. It should be understood that the preferred embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.
[0016] Example 1: A method for testing the synergistic effect of a mutual solvent and a surfactant for cementing mentioned in the present invention, the technical scheme of which is: comprising the following process: First, the flushing solution was prepared according to the designed formula, and the formula containing only surfactant was designed to facilitate the comparison of the synergistic effect; Secondly, prepare oil-based mud and use mud with different oil-water ratios for comparison; in addition, heat the oil-based mud according to site requirements, and pour the flushing liquid into the test cup for testing after high-temperature curing; Then, the prepared flushing liquid is added to the oil-based mud in batches in a quantitative manner. The conductivity of the non-conductive oil-based mud is 0 μs / cm. When the conductivity becomes the conductivity of the water-based mixture and is greater than 800 μs / cm, the synergistic effect of the mutual solvent and the surfactant is quantitatively evaluated by adding the flushing liquid volume ratio.
[0017] Among them, the wetting test of the flushing solution mentioned above with only the mutual solvent (KCM036) is as follows: 0gal KCM035+2gal KCM036+40gal water, wherein the mutual solvent KCM036 is ethylene glycol monobutyl ether, and the mutual solvent is a colorless transparent liquid organic solvent with good emulsification and penetration effects, so that it has good oil removal ability.
[0018] The sample density of oil-based mud is 1.38 g / cm 3 , solid phase volume content is 44%, oil phase volume is 45%, and water phase volume is 11%.
[0019] The device for implementing the test includes a silicone rubber heating plate, a constant speed stirrer, a conductivity tester, an electrode, and a stirring cup 6. The silicone rubber heating plate device includes a power supply 1, a wire 2, a temperature controller 3, and a silicone plate heater 4. The heating temperature and heating rate can be set to 25-95°C. The constant speed stirrer includes a speed regulator 5, and the stirring speed can be set to 4000rpm, 12000rpm, and manual speed adjustment. The conductivity tester has a test range of 0.5-200μs / cm, and the electrode is a DJS-1.0 Bosnia and Herzegovina electrode. The 1000ml stirring cup base has a four-claw stirring blade, which can be equipped with a speed-adjustable stirrer.
[0020] The specific experimental steps are as follows: (1) Adjust the temperature controller to the required test temperature and start the heating button; (2) Pour 200 mL of preheated oil-based drilling fluid into the mud cup. The conductivity meter electrode should be inserted into the oil-based mud, and the oil-based mud should not pass through the electrode; (3) Adjust the speed knob to make the agitator rotate until the vortex formed by the drilling fluid can be seen at the top of the center axis of the agitator blade. At this time, the conductivity value is extremely low, almost 0μs / cm; (4) After the oil-based drilling fluid reaches the required experimental temperature and stabilizes, add 10 mL of flushing fluid to the oil-based drilling fluid in the slurry cup each time, continue stirring until the reading is stable, and then read the conductivity value at this time; (5) When the conductivity value reaches 2000 or above, it indicates that the water-based flushing fluid has a wetting reversal effect on the oil-based drilling fluid.
[0021] (6) Draw a curve with the volume fraction of the water-based spacer liquid in the total liquid as the horizontal axis and the conductivity of the mixed liquid as the vertical axis. From the curve, we can get the volume fraction of the water-based flushing liquid added when the conductivity is the highest value.
[0022] From the experimental results ( Figure 3 ) It can be seen that the wetting reversal ratio of the oil-based mud with only mutual solvent is 62%, and the maximum conductivity is 2500μs / cm. The reversal ratio is large, the reversal time is long, and the wetting effect is not obvious.
[0023] In addition, the present invention evaluates the wetting ability of the water-based spacer fluid on the oil-based drilling fluid by continuously testing the conductivity of the mixture under the experimental temperature and shear rate. The specific principle is: the oil-based drilling fluid is not conductive, while the water-based spacer fluid is conductive. When a variable amount of water-based spacer fluid is added to a quantitative amount of oil-based drilling fluid, the conductivity of the stirred mixture will change. This change can be measured in numbers, and the influence of different added amounts of surfactants and mutual solvents on the reversal rate is evaluated by volume ratio.
[0024] The formula of the isolation liquid is: 893.57g water + 10.7g defoamer + 2111.3g barite + 35.7ml KCM035 + 71.4ml KCM036. The compatibility test procedure is as follows: 1) Prepare isolation fluid and cement slurry according to the formula.
[0025] 2) The isolation liquid and cement slurry are cured at normal pressure at the same time, the room temperature is raised to 190°F, and cured for 30 minutes.
[0026] 3) Mix the spacer liquid and cement slurry in the ratio of 95:5, 75:25:50:50, 25:75, and 5:95 (by volume) (put the liquid with a smaller volume first, then the liquid with a larger volume), stir evenly with a glass rod, and observe whether there is any thickening phenomenon.
[0027] 4) After stirring evenly, use a rotational viscometer to measure the readings from high to low speed.
[0028] During the experiment, five ratios were tested one by one, and the cement paste and spacer fluid were continuously cured in an atmospheric curing kettle at 190°F.
[0029] Example 2: A test method for the synergistic effect of a mutual solvent and a surfactant for cementing mentioned in the present invention. In this example, the flushing fluid used in the wetting test with only a surfactant (KCM035) added is used. The experimental formula is as follows: 2gal KCM035+0gal KCM036+40gal water, wherein KCM035 is a nonionic composite surfactant having both lipophilic and hydrophilic properties, wherein the lipophilic group is composed of long-chain hydrocarbon groups such as siloxane groups and straight-chain alkyl groups, and the hydrophilic group is polyoxyethylene ether.
[0030] The oil-based mud and experimental steps used in the experiment are the same as those in Example 1, but the formula is different. From the experimental results ( Figure 4 ), the reversal ratio of the oil-based mud with only surfactant added is about 52%, and the maximum conductivity is 2500μs / cm. The reversal ratio is smaller than that with only mutual solvent added, the reversal time is relatively short, and the wetting effect is not very obvious.
[0031] Example 3: A method for testing the synergistic effect of a mutual solvent and a surfactant for cementing mentioned in the present invention. The wettability test of the flushing fluid used in this example is performed by adding a surfactant and a mutual solvent to the flushing fluid at the same time. The formula is: 1gal KCM035+2gal KCM036+39gal water; KCM035 and KCM036 refer to Examples 1 and 2, The oil-based mud and experimental steps used in the experiment are the same as those in Example 1, but the formula is different. From the experimental results ( Figure 5) It can be seen that when the surfactant and the mutual solvent are added to the flushing liquid at the same time, the ratio of the two is 1:2, and the wetting reversal ratio of the oil-based mud is 41%, which is significantly smaller than that of Example 1 and Example 2. In addition, the maximum conductivity is 7800μs / cm, the reversal is rapid, and the wetting effect is more obvious. The mixture after wetting is basically close to water, and the synergistic effect of the surfactant and the mutual solvent is obvious.
[0032] Example 4: A test method for the synergistic effect of a mutual solvent and a surfactant for cementing mentioned in the present invention. The wettability test of the flushing liquid used in this example is performed by adding a surfactant and a mutual solvent to the flushing liquid at the same time, and adjusting the ratio of the two. The experimental formula is: 2gal KCM035+4gal KCM036+39gal water, KCM036 refers to Examples 1 and 2, and KCM035 uses sodium fatty alcohol polyoxyethylene ether sulfate.
[0033] The oil-based mud used in the experiment and the experimental steps are the same as those in Example 1, but the formula is different. From the experimental results ( Figure 6 ) It can be seen that when the surfactant and the mutual solvent are added to the flushing liquid at the same time, the ratio of the two is 2:4, the wetting reversal ratio of the oil-based mud is 30%, which is significantly smaller than that of Example 1, Example 2 and Example 3, and the maximum conductivity is 8500μs / cm, the reversal is rapid, the wetting effect is more obvious, and the mixture after wetting is close to water. The synergistic effect of increasing the addition amount of surfactant and mutual solvent is more obvious. Example
[0034] The spacer fluid and cement slurry were prepared according to the above spacer fluid formula and cement slurry formula, and the compatibility of the spacer fluid and cement slurry was tested according to the compatibility test procedure. The test results are as follows, and the curve is shown in Figure 7 ;
[0035] The above are only some preferred embodiments of the present invention. Any person skilled in the art may modify the above technical solutions or modify them into equivalent technical solutions. Therefore, the corresponding simple modifications or equivalent transformations made according to the technical solutions of the present invention shall fall within the scope of protection claimed by the present invention.
Claims
1. A method for testing the synergistic effect of a mutual solvent and a surfactant for cementing, characterized in that: The process includes: First, the flushing liquid is prepared according to the designed formula, and the formula containing only surfactant, only mutual solvent, or both surfactant and mutual solvent is designed, and the formula with different addition ratios of the two is designed to facilitate the comparison of the synergistic effect; Secondly, prepare oil-based mud and use mud with different oil-water ratios for comparison; in addition, heat the oil-based mud according to site requirements, and pour the flushing liquid into the test cup for testing after high-temperature curing; Then, the prepared flushing liquid is added to the oil-based mud in batches in a quantitative manner. The conductivity of the non-conductive oil-based mud is 0 μs / cm. When the conductivity becomes the conductivity of the water-based mixture and is greater than 800 μs / cm, the synergistic effect of the mutual solvent and the surfactant is quantitatively evaluated by adding the flushing liquid volume ratio.
2. The method for testing the synergistic effect of a mutual solvent and a surfactant for cementing according to claim 1, characterized in that: The flushing solution adopts the wetting test with only the mutual solvent KCM036 added, and its formula is as follows: 0gal KCM035+2gal KCM036+40gal water; KCM036 is ethylene glycol monobutyl ether; The sample density of oil-based mud is 1.38 g / cm 3 , solid phase volume content is 44%, oil phase volume is 45%, and water phase volume is 11%.
3. The testing method for the synergistic effect of mutual solvent and surfactant for cementing according to claim 1, characterized in that: The flushing liquid adopts the wetting test with only the surfactant KCM035 added, and its formula is as follows: 2gal KCM035+0gal KCM036+40gal water, wherein KCM035 is a non-ionic composite surfactant.
4. The method for testing the synergistic effect of mutual solvent and surfactant for cementing according to claim 1, characterized in that: The wettability test of the flushing liquid is carried out by adding a surfactant and a mutual solvent to the flushing liquid. The formula is: 1gal KCM035+2gal KCM036+39gal water, KCM035 is a non-ionic composite surfactant, and KCM036 is ethylene glycol monobutyl ether.
5. The method for testing the synergistic effect of mutual solvent and surfactant for cementing according to claim 1, characterized in that: The wettability test of the flushing liquid is carried out by adding a surfactant and a mutual solvent to the flushing liquid. The formula is: 2gal KCM035+4gal KCM036+39gal water, KCM035 is a non-ionic composite surfactant, and KCM036 is ethylene glycol monobutyl ether.
6. The method for testing the synergistic effect of a mutual solvent and a surfactant for cementing according to claim 3, 4 or 5, characterized in that: The nonionic composite surfactant has the characteristics of lipophilic and hydrophilic amphiphilicity, the lipophilic group of which is composed of a long-chain hydrocarbon group, and the hydrophilic group is polyoxyethylene ether.
7. The method for testing the synergistic effect of mutual solvent and surfactant for cementing according to claim 6, characterized in that: The long-chain hydrocarbon group includes a siloxane group and a straight-chain alkyl group.
8. The method for testing the synergistic effect of mutual solvent and surfactant for cementing according to claim 7, characterized in that: Specific steps as follows: 1) Prepare the flushing solution according to the recipe; 2) Measure 100 ml of uniform oil-based mud V0 and put it into the mixing cup; 3) The conductivity meter's electrodes should be inserted into the oil-based mud, and the oil-based mud should not pass through the electrodes; 4) Turn on the speed regulator start switch of the stirring device and adjust the speed to the liquid level and vortex; 5) After the conductivity meter test results are stable, read the conductivity reading of the oil-based mud; 6) Add V ml of flushing fluid to the oil-based mud and record the conductivity data until the reading stabilizes; 7) Calculate according to the formula: V%=V*100% / (V+V0); Wherein, V%, is the percentage of power washing volume to total liquid volume, %; V, volume of flushing solution added, ml; V0, oil-based mud volume, ml.